DESCRIPTION OF WORKING ENVIRONMENT SANITATION IN THE OFFICE BUILDING OF THE WARSHIP DIVISION PT PAL INDONESIA (PERSERO) - Anisa Nur Afifah; Khuliyah Candraning Diyanah (The Indonesian Journal of Public Health, 2021)
ABSTRACTSanitation is a public health effort that emphasizes mastery of various environmental factors that affect the degree of human health. Agencies that have a good and comfortable work environment will support improved performance for their employees. This study aimed to identify the description of working environment sanitation in the warship division office building at PT PAL INDONESIA (PERSERO). This research was observational. From the entire office space in the Warship Division, the five rooms with the most employees were selected for this research. The research instrument was an observation sheet with variables of building facilities, water supply, toilet, disease vector, lighting, noise, temperature, and humidity. Data analysis was performed descriptively with scoring. The results showed that four out of the five rooms (80%) that were observed had poor sanitation because they had a score of less than 75%. The results showed that the variables that were included in the criteria of lack of sanitation were toilets, lighting, temperature, and humidity. Suggestions given for the company are for building facilities, water supply, noise, and disease vector to be maintained because they are included in good sanitation criteria. Toilets, lighting, temperature, and humidity need to be fixed immediately, and reported to the officer responsible if things that can reduce the quality of office sanitation are observed. Keywords: sanitation, indoor air quality, work environment